Investigation of UF membranes fouling and potentials as pre-treatment step in desalination and surface water applications - Christopher Wright (Desalination, 2018)
The surface fouling of UF membranes used upstream as pre-treatment stage is critical for the long-term stability of the subsequent treatment stage (NF/RO membranes). In this paper, an attempt was made to probe and compare the potential of versatile UF membranes structures in terms of flux decline and selectivity, for more convenient pretreatment membranes selection. The role of polyethersulfone (PES) host polymer concentration, on the morphology and surface characteristics of asymmetric flat sheet ultrafiltration (UF) membranes, has been comprehensively investigated. Distinctly, as the casting solution viscosity decrease, a higher pore size, pore size distribution and pure water flux was observed along with lower mechanical properties and wider cross-section morphologies. However, this impact was trivial on water contact angle, surface roughness parameters and charge negativity of the membrane. To further assess the potential performance of the hand-made fabricated membranes, they were systematically evaluated against three organic model foulants with dissimilar origins; humic acid (HA) – as natural organic matters (NOM), sodium alginate (NaAlg) – as polysaccharide, and bovine serum albumin (BSA) – as protein, under different initial feed concentration and pH chemistry. A disparate fouling behavior was observed depending on the membrane characteristics and the organic model foulant used. Depending on the UF membrane cut-off used, lower MWCO membranes, PES22 (6 kDa) and PES20 (10 kDa) exhibited a negligible relative flux decline while extremely low relative flux patterns were observed in the filtration with the 100 kDa membrane (PES16), as a result of one or more pore blocking mechanisms observed.